REDUCING STIGMATISATION AND DISCRIMINATION THROUGH PROVISION OF CARE AND SUPPORT TO FELLOW PERSONS LIVING WITH THE HUMAN IMMUNODEFICIENCY VIRUS (PLHIV) IN GHANA: THE CASE OF THE ‘MODELS OF HOPE’ - Avornyo, Raphael (European Scientific Journal, ESJ, 2014)
In view of the stigma attached to HIV and AIDS, many family members and friends of Persons Living with HIV and AIDS (PLHIV) neglect them. In Ghana, some PLHIV voluntarily provide care and support for other PLHIV newly diagnosed of suffering from HIV. This study sought to ascertain what motivates them to undertake this task in Ghanaian hospitals, clinics and homes and what impact they make. Qualitative and quantitative methods were adopted for the study. Data for the study were obtained from 120 purposively selected PLHIV serving as ‘models of hope’. Data collection methods employed for this study were questionnaire administration and in-depth interviewing. Quantitative data of the study were analysed using the Statistical Product for Service Solutions (SPSS), version 17.0. Additionally, qualitative data were manually analysed. The theoretical framework for the study is the hope theory. A major result of the study was that the respondents were motivated to care for and support their fellow PLHIV newly diagnosed of suffering from HIV with a view to helping them have some hope and live positively with HIV. Although they were faced with financial problems, stigmatisation and discrimination, the refusal of some clients to religiously take their drugs after adherence counselling, etc., they still provided the needed care and support. Through their services most of their clients gain a lot of hope, particularly when they regain their health, live positively with HIV and overcome self-stigma. The study recommends that stakeholders encourage these ‘models of hope’ by giving them adequate training and consistently motivating them through the recognition they give them.